Salivary endocannabinoids and N -acylethanolamines upon mastication of a semisolid food: implications in fat taste, appetite and food liking - Mennella, Ilario; Di Monaco, Rossella; Balazy, Adriana; Ferracane, Rosalia; Miele, Nicoletta A.; Cavella, Silvana; Vitaglione, Paola (Food & function, 2018)
This study aimed to evaluate whether salivary endocannabinoid (EC) and N -acylethanolamine (NAE) concentrations upon mastication of a semisolid food were involved in the sensory perception of fat taste, food liking and appetite in humans. A fat-enriched (FEP) and a low-fat control (CP) pudding were developed and used in a randomized cross-over study with 19 healthy volunteers. The study protocol combined a Modified Sham-Feeding (MSF) with a multiple-spoon Temporal Dominance of Sensations method. Subjects masticated and expectorated 10 spoons of the pudding and selected the dominant sensations among a list of attributes. Saliva samples, appetite and food liking scores were collected at baseline, immediately after the MSF of the pudding and every 5 min until 20 min after MSF. Salivary concentrations of all monitored ECs and NAEs increased during pudding mastication compared to baseline (except for palmitoylethanolamide with FEP). The raise was lower with FEP than with CP for all compounds except for 2-arachidonoylglycerol whose increase was higher than the other compounds and independent of pudding type. Salivary N -arachidonoylethanolamine, linoleoylethanolamide and palmitoylethanolamide were significantly lower at 10 and 20 min after MSF of FEP than CP. Fatty taste at the 2 nd spoon and creaminess at the 5 th spoon were perceived as dominant with FEP whereas only wateriness was dominant with CP at the 2 nd spoon. No difference between puddings for individual appetite or food liking over the 20 min of the protocol was recorded. During mastication of a semisolid fat-enriched food, the fatty taste and the creaminess were perceived as dominant. Salivary ECs and NAEs were not associated with the individual perception of fatty taste, pudding liking and appetite sensations.